The Potent and Broadly Neutralizing Human Dengue Virus-Specific Monoclonal Antibody 1C19 Reveals a Unique Cross-Reactive Epitope on the bc Loop of Domain II of the Envelope Protein - Scott A. Smith (American Society for Microbiology, 2013)
ABSTRACT Following natural dengue virus (DENV) infection, humans produce some antibodies that recognize only the serotype of infection (type specific) and others that cross-react with all four serotypes (cross-reactive). Recent studies with human antibodies indicate that type-specific antibodies at high concentrations are often strongly neutralizing in vitro and protective in animal models. In general, cross-reactive antibodies are poorly neutralizing and can enhance the ability of DENV to infect Fc receptor-bearing cells under some conditions. Type-specific antibodies at low concentrations also may enhance infection. There is an urgent need to determine whether there are conserved antigenic sites that can be recognized by cross-reactive potently neutralizing antibodies. Here, we describe the isolation of a large panel of naturally occurring human monoclonal antibodies (MAbs) directed to the DENV domain II fusion loop (FL) envelope protein region from subjects following vaccination or natural infection. Most of the FL-specific antibodies exhibited a conventional phenotype, characterized by low-potency neutralizing function and antibody-dependent enhancing activity. One clone, however, recognized the bc loop of domain II adjacent to the FL and exhibited a unique phenotype of ultrahigh potency, neutralizing all four serotypes better than any other previously described MAb recognizing this region. This antibody not only neutralized DENV effectively but also competed for binding against the more prevalent poor-quality antibodies whose binding was focused on the FL. The 1C19 human antibody could be a promising component of a preventative or therapeutic intervention. Furthermore, the unique epitope revealed by 1C19 suggests a focus for rational vaccine design based on novel immunogens presenting cross-reactive neutralizing determinants. IMPORTANCE With no effective vaccine available, the incidence of dengue virus (DENV) infections worldwide continues to rise, with more than 390 million infections estimated to occur each year. Due to the unique roles that antibodies are postulated to play in the pathogenesis of DENV infection and disease, there is consensus that a successful DENV vaccine must protect against all four serotypes. If conserved epitopes recognized by naturally occurring potently cross-neutralizing human antibodies could be identified, monovalent subunit vaccine preparations might be developed. We characterized 30 DENV cross-neutralizing human monoclonal antibodies (MAbs) and identified one (1C19) that recognized a novel conserved site, known as the bc loop. This antibody has several desirable features, as it neutralizes DENV effectively and competes for binding against the more common low-potency fusion loop (FL) antibodies, which are believed to contribute to antibody-mediated disease. To our knowledge, this is the first description of a potent serotype cross-neutralizing human antibody to DENV.